Ovarian cancer treatment: what is new. (1st October 2003) - Poveda, A.
Abstract : Ovarian cancer is still the fourth cause of death by cancer among women and the most fatal among gynecological tumors. The purpose of this symposium is, year after year, to report and discuss the new developments in the treatment of patients with ovarian cancer, the majority of whom still present with advanced disease. It also tries to make it clear to the participants what is evidence-based and what is not. Mature data of both classic studies like GOG-111, OV-10, and more recent studies like GOG-158, AGO-OVAR-3, and the intergroup paclitaxel/epirubicin/carboplatin (TEC) versus paclitaxel/carboplatin (TC) study have been presented. Other current controversial issues included in this edition were sequential single-agent versus simultaneous administration of combination chemotherapy, the role of combination chemotherapy in second-line treatment, the role of consolidation therapy, the role of anthracyclines in the treatment, and cost-effectiviness studies in ovarian cancer. Although the main topic of the symposium is advanced disease, this edition included the results of two parallel randomized studies (ACTION and ICON1) on the treatment of early disease. In addition, new trends in early detection of ovarian cancer have been updated. The pace of new agent development has increased, and it would be helpful to have more efficient preclinical models and early phase-clinical trials to guide the selection of active agents for phase III evaluation. Reaching international consensus is a challenge but offers the opportunity to test multiple regimens more efficiently against a single-control population, rather than conducting multiple smaller studies with redundant internal controls. If indeed answers to the relevant questions are to be obtained more quickly, then, a network of current national or international groups could potentially facilitate this.